NLTE CALCULATION FOR O II - Korotin, S. A. (Одеські астрономічні публікації, 2017)
The Kurucz's atmospheric models and a modified version of the MULTI code are applied in a NLTE investigation of the O II spectrum. It is shown that previously performed analyses based on the use of lightly line- blanketed Gold models give results that are in variance with those based on the use of the more heavily blanketed Kurucz's models. One result of our calculations is a number of useful relationships between the NLTE oxygen abundance, line equivalent width, and stellar atmospheric parameters.